2018
DOI: 10.1155/2018/2374327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermocycling, Teeth, and Polymerization Methods on Bond Strength Teeth-Denture Base

Abstract: Objective To evaluate the shear bond strength between different artificial teeth and denture base polymerized by two polymerization methods submitted to thermocycling. Materials and Methods Two acrylic resins were selected according to the polymerization method (water-bath and microwave), and four different artificial teeth (Biotone, Dentsply; Trilux, Vipi Dent; Premium 8, Heraeus Kulzer; Soluut PX, Yamahachi) were also tested. The polymerization of the acrylic resin was performed by using conventional cycle (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 23 publications
1
28
0
1
Order By: Relevance
“…7 Findings related to the bond strength between denture base materials and artificial teeth vary. [8][9][10][11][12][13][14][15][16] As some studies have already reported, different types of prefabricated teeth also showed differences in the shear bond strength. 4,17 Advancements in technology have ensured digital methods for denture base fabrication (computer-aided design/ computer-aided manufacturing [CAD/CAM]), including subtractive (milling) and additive technologies (three-dimensional [3D] printing).…”
Section: Introductionmentioning
confidence: 90%
“…7 Findings related to the bond strength between denture base materials and artificial teeth vary. [8][9][10][11][12][13][14][15][16] As some studies have already reported, different types of prefabricated teeth also showed differences in the shear bond strength. 4,17 Advancements in technology have ensured digital methods for denture base fabrication (computer-aided design/ computer-aided manufacturing [CAD/CAM]), including subtractive (milling) and additive technologies (three-dimensional [3D] printing).…”
Section: Introductionmentioning
confidence: 90%
“…The combination of a rougher surface/sandblasted surface and bond agent application significantly improved the shear bond strength between the repair and the tooth in composite resin. Nevertheless, this protocol showed similar result to only applying bond agent for acrylic resin teeth [7,19].…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, there is a chemical interaction between the resin base and artificial teeth [3]. Regarding disadvantages, acrylic resin artificial teeth exhibit often-occlusal wear, which leads to decreased masticatory efficiency and loss of vertical dimension [5].They also present clinical problems, as they suffer remolding of worn occlusal surfaces in denture teeth [5,6], and fractures or debonding from the prosthesis base [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that the present study showed higher bond strength values after the storage in artificial saliva. However, also the thermal cycles in the oral cavity could have an effect on adhesion values [ 48 ]. Therefore, further studies are needed in order to test this variable.…”
Section: Discussionmentioning
confidence: 99%